Turismo: la reestructuración cultural - Ascanio, Alfredo (PASOS Revista de Turismo y Patrimonio Cultural, 2003)
The tourism historically has always been a social phenomenon related to the culture, therefore often has contributed to its restitution. Its impacts have been positive and negative and because of it has been so polemic its development in the different countries where has had greater presence. The protective function and socialization of the culture has been important in the tourism development for centuries and including in the present with greater reason. The only way to generate politics upon the cultural tourism is carrying out first the basic research to know the impacts and to decide consequently